2014
DOI: 10.1159/000368227
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of Modern Recording Devices for Speech Analysis: Smartphone, Landline, Laptop, and Hard Disc Recorder

Abstract: Background: Large-scale multi-site experimental and clinical speech protocols require high-fidelity, easy-to-use speech recording technologies. However, little is known about the reliability and comparability of affordable, portable and commonly used technologies with traditional well-validated devices (e.g., a hard disc recorder with a high-quality microphone). Objective: To examine the comparability of speech and voice samples acquired from protocols involving high- and low-quality devices. Methods: Speech s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
0
34
0
3
Order By: Relevance
“…In addition, the design of the user interface could also affect the quality of recordings, e.g., by including empty periods in the recordings to estimate ambient noise, or by providing feedback to the participant in the form of beeps, text, or voice prompts to improve task compliance. Several recent papers have examined the comparability of audio recordings made across different devices, including smartphones [19][20][21][22][23]. While several studies found that smartphones yield recordings of acceptable quality compared to standard microphones [20,22,24], others reported mixed findings with the differences relating to the particular audio outcome measures used [19,21,23].…”
Section: Demonstrating Speech Differences Based On Clinical Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the design of the user interface could also affect the quality of recordings, e.g., by including empty periods in the recordings to estimate ambient noise, or by providing feedback to the participant in the form of beeps, text, or voice prompts to improve task compliance. Several recent papers have examined the comparability of audio recordings made across different devices, including smartphones [19][20][21][22][23]. While several studies found that smartphones yield recordings of acceptable quality compared to standard microphones [20,22,24], others reported mixed findings with the differences relating to the particular audio outcome measures used [19,21,23].…”
Section: Demonstrating Speech Differences Based On Clinical Diagnosismentioning
confidence: 99%
“…Several recent papers have examined the comparability of audio recordings made across different devices, including smartphones [19][20][21][22][23]. While several studies found that smartphones yield recordings of acceptable quality compared to standard microphones [20,22,24], others reported mixed findings with the differences relating to the particular audio outcome measures used [19,21,23]. A few studies have examined the effects of ambient noise on voice recordings, with one recommending a threshold of 50 dBA as an acceptable level for their particular speech tasks and outcome measures [21,25].…”
Section: Demonstrating Speech Differences Based On Clinical Diagnosismentioning
confidence: 99%
“…Obtaining a high fidelity recording of the speech signal and appropriate application of spectral analysis are essential to the acoustic analysis of speech. Information on microphone and recorder specifications needed for speech recordings is available in several papers (Hunter, Spielman, Starr, and Popolo, 2007; Plichta, n.d.; Sustainable Heritage Network, 2006; Švec & Granqvist, 2010; Vogel, Rosen, Morgan, & Reilly, 2015). For spectral analysis of formant pattern, the commonly used methods are the Fast Fourier Transform (FFT) and Linear Predictive Coding (LPC).…”
Section: 0 General Issues Of Speech Recording and Analysismentioning
confidence: 99%
“…Smartphones are increasingly used to collect speech data for acoustic analysis, and several authors have suggested that smartphones have sufficient reliability for voice analysis with a clinical purpose [1]- [6]. [7] took a less optimistic stance on this and argued that previous analyses partly rested on false assumptions about the nature of the problem.…”
Section: Introductionmentioning
confidence: 99%